Cycling Down Under: a comparative analysis of bicycling trends and policies in Sydney and Melbourne. - Pucher, John; Garrard, Jan; Greaves Stephen (My University, 2010)
In spite of their colder climate, Canadians cycle about three times more than Americans. The main reasons for this difference are Canada s higher urban densities and mixed-use development, shorter trip distances, lower incomes, higher costs of owning, driving and parking a car, safer cycling conditions, and more extensive cycling infrastructure and training programs. Most of these factors result from differences between Canada and the United States in their transport and land-use policies, and not from intrinsic differences in history, culture or resource availability. That is good news, since it suggests the possibility of significantly increasing cycling levels in the United States by adopting some of the Canadian policies that have so effectively promoted cycling and enhanced its safety. difu
Keywords: Fahrradverkehr; Verkehrsverhalten; Verkehrsmittelwahl; Stadtverkehr; Individualverkehr; Fahrradnutzung; Radverkehrsanteil; Radverkehrspolitik; Vergleichsstudie; Einflussfaktor; Nachhaltigkeit